A Creative Model for an Interdisciplinary Approach to Service-Learning. (16th June 2021) - Marx, Meghan A; Glaser, Rivka L; Moran, Christine E; Tucker, Kimberly Pause
Synopsis: The biological sciences are inherently interdisciplinary and important advances in biology cannot be made without collaboration. Despite the increasing emphasis on interdisciplinarity in higher education, science courses only rarely extend to content outside of the STEM discipline. Classes are typically taught by one faculty member in one discipline. To demonstrate relevance while addressing genuine community needs, faculty can use service-learning in their courses. Service-learning is an experiential learning strategy where students learn course content and additional relevant skills through completing service with a community partner. Community needs are frequently beyond the scope of a single course or discipline. In order to better meet community needs, an interdisciplinary collaboration provides a more comprehensive experience that highlights the application and interconnection of course content. This article presents a generalisable model for successful interdisciplinary collaborations. While the nature of course scheduling, academic department structure, and faculty workload can be barriers to collaboration between faculty, they are not insurmountable and accomplishable within this framework. The benefits to the students and the community far outweigh navigating these challenges. Using an interdisciplinary approach in teaching will not only enrich course content and expand student learning in multiple areas, but also increase collaboration within the academy while better meeting community needs.